Ungkapan Lisan Melayu Kepulauan Riau: Kajian Transitivitas - Medri Osno (SUAR BETANG, 2019)
This study aims at finding local wisdom in the oral tradition of Kepulauan Riau Malay which is interpreted as transitivity through processes, participants, and circumstance. This is a qualitative research with descriptive statistics. Data collection applies the method of observation attentively, referring to Uninvolved Conversation Observation technique and Note Taking techniques. The transitivity analysis method uses a combination of methods that refer to the Halliday LFS analysis model. The findings of this study are that UMKR through the transitivity system has diverse social processes. This diversity determines and is determined by language structured based on the needs of participants. The participants that appear in the form of living objects and inanimate objects, while the participant role in accordance with the type of process that binds it. Process is the core of activity in clauses realized by verbs. The percentage of process appearance is dominated by relational processes 17.3%, material 15.2%, verbal 2.1%, behavior 2.8%, mental 3.5%, and form 6.2%. The dominance of the relational and material processes indicates that the character of Kepulauan Riau Malay in life at the social level always relates to the patterns (ways) that they have agreed on in their environment. This relationship is intensive between them. In semantics, this activity is realized in the form of concrete actions.